Labor Market Opportunities and Women's Decision Making Power within Households - Kaveh Majlesi (Lund University, School of Economics and Management, Department of Economics, 2014)
Despite the perceived importance of labor market opportunities in shaping married women's outside option, and their bargaining power within households as a result, this link has received very little empirical attention. Using longitudinal data on who makes the decision on a wide range of issues within Mexican households and data from the administrative records of the Mexican Social Security Institute, this paper identifies the effects of relative changes in labor market opportunities for men and women on both working and non-working women's decision making power. The implications for children's health are also investigated. Using the differential effects of China's admission to the WTO across Mexican industries, I check the robustness of my results.
Keywords: D13; J13; J16; J23; O14; 330; Bargaining power; Labor demand; Women; China